2021
DOI: 10.1002/admt.202100222
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Direct Laser Writing of 3D Graphene‐Laden Microstructures

Abstract: A wide range of applications rely on the ability to integrate electrically conductive microstructures with microfluidic channels. To bypass the planar geometric restrictions of conventional microfabrication processes, researchers have recently explored the use of “Direct Laser Writing (DLW)”—a submicron‐scale additive manufacturing (or “3D printing”) technology—for creating conductive microfeatures with fully 3D configurations. Despite considerable progress in the development of DLW‐compatible photomaterials, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…As a consequence, Q-factor and resonance frequency of suspended rGO resonators are lower than that of graphene. In addition, liquid phase reduced graphene oxide can be printed on the targeted location and polymerized by two-photon polymerization by direct laser writing [220]. This enables production of interesting features of coils in micron sizes.…”
Section: Other Approachesmentioning
confidence: 99%
“…As a consequence, Q-factor and resonance frequency of suspended rGO resonators are lower than that of graphene. In addition, liquid phase reduced graphene oxide can be printed on the targeted location and polymerized by two-photon polymerization by direct laser writing [220]. This enables production of interesting features of coils in micron sizes.…”
Section: Other Approachesmentioning
confidence: 99%
“…DLW entails scanning a femtosecond pulsed IR laser in a point-by-point, layer-by-layer manner to selectively crosslink a photocurable material in target locations via two-photon (or multiphoton) polymerization to ultimately produce 3D objects comprising cured photomaterial with feature resolutions down to the 100 nm range. [43][44][45][46] Previously, researchers have demonstrated the utility of using DLW to print MNA master molds, which can then be used to replicate solid MNAs with drug coatings [47][48][49][50] or solid MNAs that are fully dissolvable. [51,52] Additionally, Rad et al reported the use of DLW to print molds and MNAs directly that include open (i.e., unenclosed) side channels.…”
Section: Introductionmentioning
confidence: 99%
“…Although relatively high specific electrical conductivities up to ≈10 6 S m −1 wt% −1 (conductivity per concentration of metallic nanoparticles) can be achieved, metal‐nanoparticle‐loaded resins produce planar structures. [ 17 ] On the other hand, MPL‐compatible composite resins containing carbon nanotubes (CNTs) [ 23–25 ] and graphene [ 26,27 ] exhibit 3D microstructures. However, these nanomaterials demonstrate low specific electrical conductivities up to only ≈200 S m −1 wt% −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Development of innovative 3D micro and nanoscale technologies in nanoelectronics, [1] micro/nanoelectromechanical systems, [2] nanophotonics, [3] micro/nanofluidics, [4] and nanobiosciences [5] requires advancements in existing light inducedadditive manufacturing techniques including electron beam lithography, [6] Digital Light Processing, [7] dip pen lithography, [8] concentration of metallic nanoparticles) can be achieved, metalnanoparticle-loaded resins produce planar structures. [17] On the other hand, MPL-compatible composite resins containing carbon nanotubes (CNTs) [23][24][25] and graphene [26,27] exhibit 3D microstructures. However, these nanomaterials demonstrate low specific electrical conductivities up to only ≈200 S m −1 wt% −1 .…”
Section: Introductionmentioning
confidence: 99%